S. Szabó József (1862-1944) pedagógusi munkássága: a „szeretet igéjével” való nevelés példája - Ágota FEHÉR (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2023)
The Work of József S. Szabó (1862–1944) as a Teacher: An Example of Education with the “Biblical Word of Love”. The spirit of the Reformed College of Debrecen has been a defining value for centuries, and it still is today, helping students to grow up and develop their best abilities. Its effectiveness is determined by dedicated teachers, who support the students with both their knowledge and personality, while their activities also provide inspiration that should be followed as an example for future educators. The teaching work of József S. Szabó, the religion teacher and Director of the Debrecen Reformed College High School between 1922 and 1929, carries rich values with the spiritual growth of both the institution and its students. The purpose of this study is to examine the life path that served as the source of this exceptional pedagogical effect and through it to support the lessons of the roots of the spirit. In the background of the processing, in addition to the relevant literature, high school bulletins and parish minutes were also used as a basis.